Strengthening the Value of Anti-Corruption Prevention in the Environment of SMA Muhammadiyah 10 Surabaya in Realizing a Superior Generation - Zaman, Akhmad Qomaru; Irnawati, Irnawati -; Islami, Trinah Asi; Nilakandi, Titis Nurrusama; Ainni, Nurul; Ramadhanti, Risma Widia (Universitas of Muhammadiyah Makassar, 2024)
This study discusses the weak understanding and internalization of anti-corruption values among students who need character education efforts to prevent corrupt behavior from an early age. The purpose of this study is to evaluate the implementation of the anti-corruption value strengthening program at SMA Muhammadiyah 10 Surabaya as a step to form a generation with integrity. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation of students, teachers, and principals. The results of the study show that the school has implemented various effective programs, such as honesty canteens, transparent management of student council funds, and habituation of the values of honesty and responsibility in learning activities. These programs have a positive impact in shaping the character of students who have integrity and anti-corruption attitudes. However, the study also found that the challenges in the form of anti-corruption materials presented are still conceptual and less relevant to students' daily lives. In conclusion, the anti-corruption value strengthening program in schools is effective, but it needs to be improved by adding simulation-based materials and real case studies to deepen students' understanding of the dangers of corruption and improve the application of values in their lives.